Speech of Figure and Imagery in Song Lyrics of “Rubik” Album by Dere - Fahrozi Raihan, Ali Muhammad Alfi (Southeast Asian Language and Literature Studies, 2024)
This research aims to (1) describe the exaggeration found in the song lyrics in Rubik album by Dere, (2) describe the imagery found in the song lyrics in Rubik album by Dere. This research uses descriptive qualitative research method with library research type. This research uses the theory of majas and imagery according to Burhan Nurgiyantoro (2019). The data in this study were taken from all words and phrases that contain majas and imagery contained in the song lyrics in Dere's Rubik album which amounted to 10 songs, namely Rubik, Rumah, Berisik, Tanya, Kota, Tumbang, Kenanga, Keluku, Jangan Pergi, and Berlagu. The data source in this research is song lyrics in Rubik album by Dere. Data collection techniques in this study used documentation techniques and reading, note-taking techniques. The data analysis technique starts with analyzing and describing the findings of the data, after that concluding the results of the analysis of the data obtained. Based on the results of the analysis, there are 10 majas, namely 1 simile, 2 metaphor, 2 personification, 1 allegory, 2 metonymy, and 2 synecdoche, and 10 imagery, namely 2 visual imagery, 2 auditory imagery, 2 motion imagery, 2 sensory imagery, and 2 olfactory imagery.